1979
DOI: 10.1111/j.1365-246x.1979.tb02569.x
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake sequences on a frictional fault model with non-uniform strengths and relaxation times

Abstract: The space and time characteristics of earthquake sequences, including a main shock, aftershocks and the recurrence of major shocks in a long time range, are investigated on a frictional fault model with non-uniform strengths and relaxation times, which is subjected to a time-dependent shear stress. Aftershocks with low stress drop take place successively in spaced regions so as to fill the gaps which have not yet been ruptured since the main shock, while those with high stress drop occur in and around the regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 33 publications
2
60
0
Order By: Relevance
“…Many other mechanisms have been proposed for this temporal decay e.g. subcritical crack growth [35], visco-elastic relaxation [36], post-seismic creep due to stress corrosion in the regions of stress concentration after the mainshock [37], static fatigue [38], pore fluid flow [39], post-seismic slip [40] and earthquake nucleation under rate-and state-variable friction [41]. In general, it is assumed that the parameters c and τ are constants and are specific to a given aftershock sequence.…”
Section: Comparison With Observations 31 the Gutenberg Richter Lawmentioning
confidence: 99%
“…Many other mechanisms have been proposed for this temporal decay e.g. subcritical crack growth [35], visco-elastic relaxation [36], post-seismic creep due to stress corrosion in the regions of stress concentration after the mainshock [37], static fatigue [38], pore fluid flow [39], post-seismic slip [40] and earthquake nucleation under rate-and state-variable friction [41]. In general, it is assumed that the parameters c and τ are constants and are specific to a given aftershock sequence.…”
Section: Comparison With Observations 31 the Gutenberg Richter Lawmentioning
confidence: 99%
“…In our case, however, the distance of the aftershock clusters was only several kilometers and the temperature would not differ significantly. Mikumo and Miyatake (1979) conducted numerical simulations and showed that the p value becomes smaller as the distribution of fault strength becomes more heterogeneous. Small-scale heterogeneities in geological structures would cause differences in frictional properties along aftershock faults.…”
Section: Earthquake Cycle Simulation Based On the Hierarchical Asperimentioning
confidence: 99%
“…At present, our knowledge of the nature, distribution and regional variation of asperities on the fault is too limited to fully test this model. However, if this model proves useful for interpreting seismicity patterns, more physical and dynamic models such as the one developed by Mikumo and Miyatake (1979) need to be introduced to study further details of seismicity patterns.…”
Section: Asperity Modelmentioning
confidence: 99%